Salivary BDNF and cortisol responses during high-intensity exercise and official basketball matches in sedentary individuals and elite players - Moreira, A.; Saldanha Aoki, M.; Schultz de Arruda, A. F.; Gomes da Silva Machado, D.; Elsangedy, H. M.; Okano, A. H. (Journal of Human Kinetics, 2018)
Salivary cortisol increases in response to stressors, including physical exertion and psychological stress associated with sports competition. In addition, stress may induce change in brain-derived neurotrophic factor (BDNF). However, there are still no data available to compare the salivary BDNF level in sedentary male individuals and elite team-sport male athletes, regularly involved in activities that require elevated attention and concentration. This information could contribute to the advance of understanding of the effect of regular exercise on the salivary level of BDNF, the pre-to-post change in salivary BDNF during exercise, and the association between salivary cortisol and salivary BDNF responses to physical exercise. Therefore, this study aimed to compare the concentration of salivary cortisol and BDNF, before and after exercise, in sedentary individuals and elite male basketball players. The sedentary group (23.0 ± 4.2 yrs) performed a high-intensity exercise protocol and the basketball players (18.6 ± 0.5 yrs) participated in three official basketball matches. Saliva samples were tested for cortisol and BDNF using ELISA. A significant increase in salivary cortisol from pre- to post-match was observed only for the basketball players (p < 0.05). Basketball players also presented a higher salivary BDNF concentration for both resting (pre) and post-physical exercise (p < 0.05); however, no change in pre- to post-exercise salivary BDNF was observed for either group (p > 0.05). Elevated BDNF in athletes may be associated to their repeated exposure to stressful competition situations. The current findings also suggest that different mechanisms might be involved in salivary cortisol and BDNF responses during physical exercise.